Factors affecting the students' interest in attending school a qualitative study done in the University of Eastern Philippines. - Bayona, Anthony Julius Floralde; de Silva, Aracelli Anne Sarmiento (Tacloban City Anthony Julius Floralde Bayona and Aracelli Anne Sarmiento de Silva, 2005)
This study was made to look into the factors that affect the students' interest in atteding school. Specifically, it drew up the respondents' socio-demographic profile in terms of sex, age, family monthly income, birth order, household size, year level, hometown, and high school graduated from, the respondents' perception of attending school, and their motivation for attending school.
The descriptive research method was used in this study. This research was conducted in the University of Eastern Philippines in Catarman, Northern Samar during the 2nd semester of the Academic Year 2004-2005. The sample of this study is composed of fifteen (15) irregular students from different year levels and courses who were purposely selected by the researchers. The data collection was done through interview.
Data were presented, analyzed and interpreted with the use of frequency counts and percentages. Result showed that all of the respondents were irregular students and failure in some of their subjects in the past semesters was the reason behind it. Majority of the respondents were interested in the course they are taking up and most of them were Bachelor of Science in Biology students. Majority of the respondents were members of religious organization but some of them do not engage in other things or activities aside from their schooling. Majority of the respondents' perception of attending school is that school is the place where a person learn everything he/she have to learn to have a good job and a bright future. A respondent also said that going to school means having allowance. The primary factor that motivates the respondents to go to school is the thought of helping their family after finishing college. The main factor that affects the students' interest in attending school is their friends or peers; the next factors are the family and money. The professors and the subjects are other factors that affect the respondents' interest in going to school. Other factors that the respondents mentioned were their subjects that according to them are boring and too hard to handle. One of the respondents said that the organization that she belongs to somehow affects her study because she is sometimes busy with their activities. Work is another factor that affects the interest of one of the respondents. And, the last factor that was mentioned by a respondent is the thought of having a good future. It greatly affects his interest in attending school.
Keywords: Motivation in education -- Philippines -- University of Eastern Philippines -- Catarman (Northern Samar).; Learning; Social Science. .